SIMULASI DAN ANALISIS EFEKTIVITAS SISTEM KEAMANAN JARINGAN MENGGUNAKAN INTRUSION PREVENTION SYSTEM (IPS) BERBASIS WAZUH - Andika Andika; Rissal Efendi, M.Kom (Universitas Citra Bangsa, 2025)
Abstract Computer network security is a crucial aspect in the digital era, especially with the growing complexity and dynamics of cyber threats. This study aims to simulate a network security system using a Wazuh-based Intrusion Prevention System (IPS), an open-source security platform that integrates threat detection, prevention, and monitoring. The research methodology involves designing network topology, configuring Wazuh as an IPS, and conducting tests to evaluate its effectiveness in detecting and mitigating security threats. The simulation results show that Wazuh is capable of identifying and preventing attacks such as brute force and Cross-Site Scripting (XSS) attacks with satisfactory accuracy. This study provides practical insights into implementing an IPS-based network security system, particularly for organizations with limited resources.